Kinematics Modeling and Simulation of Wheel-foot Hybrid Walking Robot - Xinxing Tang; Deyong Zhang; Rui Wang; Chengzhi Su; Fangyuan Han (Jixie chuandong, 2021)
Combining the advantages of the foot robot and the wheeled robot，a wheel-foot hybrid walking robot configuration based on 2 (6-UPUR+3P) hybrid legs is proposed，and the kinematics modeling and simulation analysis of the robot are carried out. Based on the spiral theory，a six-dimensional motion spiral system of a single branch of the parallel leg of the robot is established. Based on this，the first-order influence coefficient matrix is obtained，and then the kinematics model of the 6-UPUR parallel leg is derived. A robot body posture adjustment algorithm is proposed to improve the motion stability of the robot body in a static walking gait. The correctness of the kinematics model obtained from the comparison of Matlab and Adams simulation is verified respectively，and the effectiveness of the body posture adjustment strategy is verified by the Adams/Simulink cosimulation，which lays the foundation for the further design of the wheel-foot hybrid walking robot control system.